Prevalence and Co-Occurrence of Lifestyle Risk Factors for Non-Communicable Diseases According to Sociodemographic Characteristics Among Adults Chilean Residents - Rios-Riquelme, M; Cofre-Bolados, C; Suarez-Reyes, M; De Moraes-Ferrari, G (Nature Research, 2021)
To examine the prevalence and co-occurrence of lifestyle risk factors for non-communicable diseases (NCDs) according to sociodemographic characteristics in Chilean residents. A cross-sectional study based on data from 5995 adults from the Chilean National Health Survey. The lifestyle risk factors included were physical inactivity, tobacco consumption, alcohol consumption, low fruits and vegetable consumption, and overweight/obesity. The most frequent risk factor was overweight/obesity (75.6%), followed by alcohol consumption (74.8%), low fruits and vegetable consumption (51.7%), physical inactivity (36.3%), and tobacco consumption (27.9%). Only 1.0% of the participants did not present any risk factor, while 9.6%, 30.4%, 34.0%, 20.3%, and 4.7% accumulated one, two, three, four, and five risk factors. Men (OR 1.56; 95% CI 1.18; 2.04), people who have secondary education (OR 1.59; 95% CI 1.20; 2.10), and those with lower household income (OR 1.39; 95% CI 1.09; 1.59) had higher odds of three or more risk factors. Associations were inverse for older adults (OR 0.57; 95% CI 0.41; 0.79) and rural geographic areas (OR 0.77; 95% CI 0.67; 0.89). The prevalence of risk factors for NCDs is fairly high in Chilean residents. Interventions may need to target these co-occurrences rather than emphasizing individual risk factors for NCDs. Interventions could further consider these co-occurrences as a potential target for population stratification. © 2021, The Author(s).